Copper-catalyzed enantioselective conjugate reduction of α,β-unsaturated esters with chiral phenol–carbene ligands - Mimura, Shohei; Mizushima, Sho; Shimizu, Yohei; Sawamura, Masaya (Beilstein Journal of Organic Chemistry, 2020)
A chiral phenol–NHC ligand enabled the copper-catalyzed enantioselective conjugate reduction of α,β-unsaturated esters. The phenol moiety of the chiral NHC ligand played a critical role in producing the enantiomerically enriched products. The catalyst worked well for various (Z)-isomer substrates. Opposite enantiomers were obtained from (Z)- and (E)-isomers, with a higher enantiomeric excess from the (Z)-isomer.
Keywords: catalyst; chiral NHC; conjugate reduction; copper catalysis; enantioselective reaction